History and its disciplinary development (Research, Society and Development, 2020)
History is a rich and fertile field of study, as it enables a detailed study of identity, cultural and social knowledge. This, as a science, is built by an immense range of themes distributed under various aspects. Since documentary sources are permeated by discourses, they are then materialized in some form of language. As a social phenomenon, language will always be discourse, since its expression is permeated by individual and collective meanings. The aim of this article is to discuss how history develops as a discipline, through bibliographical research. In order to discuss, we seek a methodological basis for the bias of Critical Discourse Analysis (hereinafter ACD), a theoretical-methodological approach that systematizes the Social Theory of Discourse, by providing scientific support for qualitative studies and that have in the text the main research material.